2021
DOI: 10.1002/smtd.202100848
|View full text |Cite
|
Sign up to set email alerts
|

Nanoprotection Against Retinal Pigment Epithelium Degeneration via Ferroptosis Inhibition

Abstract: various biological roles, including transepithelial transporting fluids and nutrients, constituting the outer blood-retinal barrier, phagocytosing photoreceptor outer segment tips, and recycling bleached visual pigments. [1] Therefore, RPE dysfunction could contribute to various ocular disorders accompanied by visual impairment and even blindness, most notably age-related macular degeneration (AMD). [2] Currently, the global prevalence of AMD in individuals aged 45 years and older is ≈8.7%. [3] Regarding AMD t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…ERG was performed as described previously [ 33 ]. To evaluate whether the hydrogel affected the visual function of mice, ERG was recorded in the mice after administration for 7 days using an Espion E3 system (Diagnosys, USA) under dim red light.…”
Section: Methodsmentioning
confidence: 99%
“…ERG was performed as described previously [ 33 ]. To evaluate whether the hydrogel affected the visual function of mice, ERG was recorded in the mice after administration for 7 days using an Espion E3 system (Diagnosys, USA) under dim red light.…”
Section: Methodsmentioning
confidence: 99%
“…Ferroptosis also plays a critical role in non-neoplastic diseases including neurogenic disease (e.g. Alzheimer's disease, amyotrophic lateral sclerosis, and Parkinson's disease) ( 6–8 ), infectious diseases ( 9 ), autoimmune diseases ( 10 ), retinal diseases ( 11 ), tissue injuries ( 12 ) and some rare disorders ( 1 ). Collectively, ferroptosis is vitally implicated in a wide variety of diseases, as well as indicative for novel approaches of disease diagnosis, treatment, and prognosis prediction.…”
Section: Introductionmentioning
confidence: 99%
“…GSH depletion can directly inactivate GPX4, as GDH is a cofactor of GPX4 . In addition, studies have shown that GSH depletion and inactivation of GPX4 cause LPO generation . Therefore, MDA levels were detected in 4T1 cells as a degradation product of LPO .…”
Section: Resultsmentioning
confidence: 99%
“…49 In addition, studies have shown that GSH depletion and inactivation of GPX4 cause LPO generation. 50 Therefore, MDA levels were detected in 4T1 cells as a degradation product of LPO. 51 The results in Figure 3F suggest that higher MDA levels were observed in cells treated with TfRA-AuNCs.…”
Section: ■ Introductionmentioning
confidence: 99%